Melanoma subtypes: genomic profiles, prognostic molecular markers and therapeutic possibilities. Issue 5 (15th February 2019) - Rabbie, Roy; Ferguson, Peter; Molina‐Aguilar, Christian; Adams, David J; Robles‐Espinoza, Carla D
Abstract: Melanoma is characterised by its ability to metastasise at early stages of tumour development. Current clinico‐pathologic staging based on the American Joint Committee on Cancer criteria is used to guide surveillance and management in early‐stage disease, but its ability to predict clinical outcome has limitations. Herein we review the genomics of melanoma subtypes including cutaneous, acral, uveal and mucosal, with a focus on the prognostic and predictive significance of key molecular aberrations. © 2018 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.